An Fc-inert PD-L1×4-1BB bispecific antibody mediates potent anti-tumor immunity in mice by combining checkpoint inhibition and conditional 4-1BB co-stimulation. (31st December 2022) - Muik, Alexander; Altintas, Isil; Gieseke, Friederike; Schoedel, Kristina B; Burm, Saskia M; Toker, Aras; Salcedo, Theodora W.; Verzijl, Dennis; Eisel, David; Grunwitz, Christian; Kranz, Lena M; Vormehr, Mathias; et al.
ABSTRACT: Immune checkpoint inhibitors (ICI) targeting the PD-1/PD-L1 axis have changed the treatment paradigm for advanced solid tumors; however, many patients experience treatment resistance. In preclinical models 4-1BB co-stimulation synergizes with ICI by activating cytotoxic T- and NK-cell-mediated anti-tumor immunity. Here we characterize the mechanism of action of a mouse-reactive Fc-inert PD-L1×4-1BB bispecific antibody (mbsAb-PD-L1×4-1BB) and provide proof-of-concept for enhanced anti-tumor activity. In reporter assays mbsAb-PD-L1×4-1BB exhibited conditional 4-1BB agonist activity that was dependent on simultaneous binding to PD-L1. mbsAb-PD-L1×4-1BB further blocked the PD-L1/PD-1 interaction independently of 4-1BB binding. By combining both mechanisms, mbsAb-PD-L1×4-1BB strongly enhanced T-cell proliferation, cytokine production and antigen-specific cytotoxicity using primary mouse cells in vitro . Furthermore, mbsAb-PD-L1×4-1BB exhibited potent anti-tumor activity in the CT26 and MC38 models in vivo, leading to the rejection of CT26 tumors that were unresponsive to PD-L1 blockade alone. Anti-tumor activity was associated with increased tumor-specific CD8 + T cells and reduced regulatory T cells within the tumor microenvironment and tumor-draining lymph nodes. In immunocompetent tumor-free mice, mbsAb-PD-L1×4-1BB treatment neither induced T-cell infiltration into the liver nor elevated liver enzymes in the blood. Dual targeting of PD-L1 and 4-1BB with a bispecific antibody may therefore address key limitations of first generation 4-1BB-agonistic antibodies, and may provide a novel approach to improve PD-1/PD-L1 checkpoint blockade.